Orbital detection of Rare Earth Elements hosted by peralkaline igneous rocks in North-western India - Hrishikesh Kumar; Aju Mohanan; Saraah Imran; P. Jayaprasad; Angana Saikia; Ajanta Goswami; Bijan Jyoti Barman; Rajesh Upadhyaya; Shubhabrata Mukhopadhyay (Journal of Geochemical Exploration, 2026)

Machine Learning-Based Prediction of Germination Index and Compost Maturity Assessment in Accelerated Garden Waste Composting - Dayanand Sharma; Hrishikesh Shivam; Saurabh Kumar; Divesh Ranjan Kumar; Warit Wipulanusat; S. Shankara Narayanan (Bioresource Technology Reports, 2026)

Transforming residues to resources: agricultural waste management for value added products, bioenergy, and sustainable economic growth - Aquiny Befairlyne T Mawthoh; Devina Seram; Haobijam James Watt; Nadir Ayrilmis; Thirukkumar Subramani; Naveen Kumar Pandurangan; Hrishikesh Patil; Jayaasree Aruljothi (Environment, Development and Sustainability, 2026)

Machine Learning Aided Kinematic Profiling of Reaching Movements Separates Spinocerebellar Ataxia type 12 and Essential Tremor - Asit Baran Bayen; Supriyo Choudhury; Suchismita Majumdar; Anna Baines; Arkaprabha Basu; Kaustav Das; Debapriya Mukherjee; Dipanwita Santra; Siddhartha Sankar Mondal; Sattwika Banerjee; Jacky Ganguly; Purba Basu; et al. (The Cerebellum, 2026)

Finite element-based strategic planning of controlled progressive collapse mechanisms in the explosive demolition of a multistory building - Ratnesh Kumar; Hrishikesh Sharma (Engineering Structures, 2026)

Indole-3-acetic acid and salicylic acid functionalized zinc oxide nanoparticles modulate physiological and biochemical responses in rice (Oryza sativa L.) - Runa Rahman; Saurabh Jyoti Hazarika; Swati Nawami Aideo; Karabi Barman; Manabendra Nath; Bhaben Tanti; Sanjib Kumar Panda; Hrishikesh Upadhyaya (Cereal Research Communications, 2026)

Abnormal Amyloidogenesis Identified in Plasma of Patients with Spinocerebellar Ataxia Type 12 - Rebecca Banerjee; Swarnava Sengupta; Jyoti Rungta; Sabbir Ansari; Sattwika Banerjee; Bishmita Biswas; Rakhi Pal; Sumantra Chattarji; Supriyo Choudhury; Hrishikesh Kumar (The Cerebellum, 2026)

Tracing Fluid Pathways Related to Hydrothermal Gold Mineralization in Hutti–Maski Schist Belt Using Imaging Spectroscopy - Hrishikesh Kumar; T. H. Syed; A. S. Rajawat; Ronak Jain; Aju Mohanan; P. Jayaprasad; S. Mukhopadhyay; Rajesh Upadhyay (Journal of the Indian Society of Remote Sensing, 2025)

Advanced hydrological assessment with SWAT+ under climate change: An integrated framework over large climate-sensitive and reservoir-regulated watershed - Debasish Mishra; Hrishikesh Singh; Munish Kumar; Mohit Prakash Mohanty (Science of The Total Environment, 2025)

Description of a new troglophilic loach, Schistura densiclava (Teleostei: Nemacheilidae) from Meghalaya, northeast India - D. Khlur Baiaineh Mukhim; Kangkan Sarma; Hrishikesh Choudhury; Rajdeep Das; Rejani Chandran; Rajeev K. Singh; Deisakee P. Warbah; Wandalin Lyngdoh; Uttam Kumar Sarkar; Dandadhar Sarma (Journal of Fish Biology, 2025)
Integrative taxonomy reveals a new troglophilic species of Schistura , from a cave‐dwelling population inhabiting stream draining (Barak–Surma–Meghna drainage) through the Krem (=cave) Mawjymbuin in East Khasi Hills of Meghalaya. Morphologically, the new species is easily distinguished from its congeners in having a combination of characters, including a unique colour pattern in the form of 14–20 greyish black to faint black bars overimposed to a black midlateral stripe on a greyish brown to pale beige (yellowish green in life); pre‐dorsal bars thin, numerous, wider than interspaces, weakly contrasted, sometimes broken and/or incomplete; bars posterior of anal‐fin base numerous and variable, mostly broken or incomplete, located on lower flank, weakly contrasted; a complete lateral line; presence of an axillary pelvic lobe; an uninterrupted thick black stripe along the base of the dorsal fin; an incomplete black basicaudal bar, dissociated, occupying median one‐third of caudal‐fin base; conspicuous black botch on the procurrent rays of the upper lobe of the caudal fin; and a type of sexual dimorphism: males with slender body, bars mostly irregular on flanks and slightly puffy cheek with greater lateral head length; females with regular‐shaped bars and swollen body. Analysis of the mitochondrial cytochrome c oxidase I (COI) gene sequence of the new species shows significant genetic divergence with p distances ranging 4.5%–13.6% from its sister species found in northeast India, supporting its report as new species. Further, this finding is also validated by phylogenetic analysis and the species delimitation approaches, Assemble Species by Automatic Partitioning (ASAP) and Poisson Tree Processes (PTP), which clearly resolved that the Schistura densiclava sp. nov. is distinct from its sister species. Although the species has been sampled from the cave, it retains a fully pigmented body and functional eyes, which are not reduced when compared to other epigean Schistura , tentatively indicating it as a troglophile. Distribution of the new species is limited to the cave, which suggests an endemism in this cave system.

Association of a kinematic measure of upper limb reaching and StartReact in chronic hemiparetic stroke - Supriyo Choudhury; Anna Baines; Swagata Sarkar; Asit Baran Bayen; Subhajit Sarkar; Mark R. Baker; Hrishikesh Kumar; Stuart N. Baker (Experimental Brain Research, 2025)
Background After stroke, recovery of upper limb reaching movements may partly depend on the level of activation of the reticulospinal tract (RST), but few clinical studies have explored this. Here we examined the association between the strength of reticulospinal connections and extent of reaching in post-stroke patients. Methods Fifteen patients (all male) with right hemiparesis who had suffered a stroke at least six months prior to the assessment were selected based on predefined selection criteria. Video recordings of the reaching task from the Action Research Arm Test (ARAT) were processed for two-dimensional kinematic analysis using the markerless motion tracking software DeepLabCut. We defined a novel Index of Elbow Extension (IoEE), and validated it by comparison between simultaneously obtained two- and three-dimensional datasets in healthy people. Strength of reticulospinal outputs was estimated using the ‘StartReact’ paradigm, which measures the speeding up of reaction time by a loud sound cue. Results We observed a significant negative correlation between the IoEE and StartReact (rho = 0.9, p < 0.05). There was no correlation in this cohort between ARAT and StartReact. Conclusion We speculate that the negative correlation between reaching performance and StartReact is a consequence of the variable compensatory activation of the reticulospinal tract (RST) in response to different levels of initial damage. This study reinforces the application of freely available computer vision technology for assessment of two- dimensional kinematics in a clinical scenario.

Recent advancements of biochar additive for construction materials, formulations technology and sustainability - Hrishikesh Kumar; M. K. Jha; N. K. Srivastava; A. K. Sarma (Innovative Infrastructure Solutions, 2025)

Decrypting proteomics, transcriptomics, genomics, and integrated omics for augmenting the abiotic, biotic, and climate change stress resilience in plants - Rashmi Choudhary; Faheem Ahmad; Cengiz Kaya; Sudhir Kumar Upadhyay; Sowbiya Muneer; Vinod Kumar; Mukesh Meena; Haitao Liu; Hrishikesh Upadhyaya; Chandra Shekhar Seth (Journal of Plant Physiology, 2025)

Integration of PRISMA hyperspectral satellite data with ground based geological investigation for mapping alteration minerals associated with the Neem-ka-Thana Cu belt in Rajasthan, India - Angana Saikia; Ajanta Goswami; Bijan Jyoti Barman; Kanishka Hans Sugotra; Hrishikesh Kumar (Remote Sensing Applications: Society and Environment, 2025)

Arsenic stress responses in sensitive and tolerant rice of North-East, India - Thorny Chanu Thounaojam; Thounaojam Thomas Meetei; Yumnam Bijilaxmi Devi; Bhaben Tanti; Sanjib Kumar Panda; Hrishikesh Upadhyaya (Cereal Research Communications, 2024)

Space and ground based spectroscopic studies and mineral chemistry of rare earth element bearing peralkaline rocks from Siwana Ring Complex, Rajasthan, India - Saraah Imran; Ajanta Goswami; Hrishikesh Kumar; Bijan Jyoti Barman; Angana Saikia (Remote Sensing Applications: Society and Environment, 2024)

Utilizing deep learning for near real-time rainfall forecasting based on Radar data - Bipin Kumar; Hrishikesh Haral; M.C.R. Kalapureddy; Bhupendra Bahadur Singh; Sanjay Yadav; Rajib Chattopadhyay; D.R. Pattanaik; Suryachandra A. Rao; Mrutyunjay Mohapatra (Physics and Chemistry of the Earth, Parts A/B/C, 2024)

Performance analysis of machine learning models for AQI prediction in Gorakhpur City: a critical study - Mandvi; Prabhat Kumar Patel; Hrishikesh Kumar Singh (Environmental Monitoring and Assessment, 2024)

Schistura sonarengaensis , a new species of cave‐dwelling loach (Teleostei: Nemacheilidae) from Meghalaya, northeast India - Dran Khlur B. Mukhim; Kangkan Sarma; Hrishikesh Choudhury; Rejani Chandran; Rajdeep Das; Rajeev K. Singh; Deisakee P. Warbah; Uttam Kumar Sarkar; Dandadhar Sarma (Journal of Fish Biology, 2024)
A new species of nemacheilid loach, Schistura sonarengaensis sp. nov., is described from three cave‐dwelling populations (Barak–Surma–Meghna drainage) in the South Garo Hills district of Meghalaya, India. The new species possesses prominent eyes but is easily distinguished from all the congeners of the genus Schistura from Barak–Surma–Meghna and adjacent rivers drainages of northeast Indian (except S. syngkai ) in having 13–26 vertically elongated to circular mid‐lateral black blotches (brownish in life) overlayered on a grayish‐black mid‐lateral stripe on a dull white or pale‐beige (golden brown in life) body. However, it can be easily distinguished from S. syngkai in having a complete (vs. incomplete) lateral line with more 72–89 (vs. 19–42) lateral‐line pored scales, greater pre‐dorsal length (48.5–53.1 vs. 41.9–44.1 %SL), a wider body at dorsal‐fin origin (11.3–16.7 vs. 9.4–10.3 %SL), greater dorsal (18.1–21.1 vs. 15.1–17.0 %SL) and lateral (20.9–24.1 vs. 17.4–18.9 %SL) head length, a wider head (14.5–18.5 vs. 11.6–13.3 %SL), and moderately forked (vs. emarginated) caudal fin. Further, molecular analysis confirms the distinctiveness of S . sonarengaensis sp. nov. from its congeners found in northeast India by significant divergences with uncorrected genetic distance ranging from 3.7% to 17.3% in the mitochondrial cytochrome c oxidase subunit I (COI) gene dataset. The phylogenetic position of the new species with its sister species was evaluated using maximum likelihood and Bayesian analysis. The species delimitation approaches assemble species by automatic partitioning (ASAP) and Poisson tree processes (PTP) utilized for testing species assignments consistently identified our test group as a distinct species from its sister species. Although the new species lacks typical morphological adaptations usually associated with a subterranean life, such as complete absence (or vestigial presence) of eyes and pigmentation, it exhibits a reduction of pigmentation when compared to the epigean congeners.

Modelling wavelength position of absorption feature using covariance weighted least square inversion - Hrishikesh Kumar; D. Ram Rajak (Advances in Space Research, 2024)

Comparative evaluation of airborne AVIRIS-NG and spaceborne PRISMA hyperspectral data in identification and mapping of altered/weathered minerals in Jahazpur, Rajasthan - Gaurav Mishra; Himanshu Govil; Arindam Guha; Hrishikesh Kumar; Shashi Kumar; Sudipta Mukherjee (Advances in Space Research, 2024)

Arsenic induced chromosomal aberrations, biochemical and morphological changes in Vigna radiata L. (Mung bean) seedlings and its amelioration by Curcumin - Zesmin Khan; Thorny Chanu Thounaojam; Jinu Devi Rajkumari; Bitupan Kumar Deka; Runa Rahman; Hrishikesh Upadhyaya (Vegetos, 2023)

Phytofunctionalized ZnO nanoparticles ameliorate water stress and its recovery in Oryza sativa L. - Soumitra Shome; Sujit Tewari; Mrinal Kanti Bhattacharya; Sanjib Kumar Panda; Hrishikesh Upadhyaya (Acta Physiologiae Plantarum, 2022)

Transporters: the molecular drivers of arsenic stress tolerance in plants - Thorny Chanu Thounaojam; Zesmin Khan; Thounaojam Thomas Meetei; Sudhakar Srivastava; Sanjib Kumar Panda; Hrishikesh Upadhyaya (Journal of Plant Biochemistry and Biotechnology, 2021)

Zinc oxide nanoparticles (ZnO-NPs): a promising nanoparticle in renovating plant science - Thorny Chanu Thounaojam; Thounaojam Thomas Meetei; Yumnam Bijilaxmi Devi; Sanjib Kumar Panda; Hrishikesh Upadhyaya (Acta Physiologiae Plantarum, 2021)

A New Schiff Base Based Fluorescent Sensor for Al(III) Based on 2-Hydroxyacetophenone and o-Phenylenediamine - Bidisha Bharali; Hrishikesh Talukdar; Prodeep Phukan; Diganta Kumar Das (Journal of Fluorescence, 2020)

Identification of Fibrinogen-Binding Proteins of Aspergillus fumigatus Using Proteomic Approach - Santosh Kumar Upadhyay; Poonam Gautam; Hrishikesh Pandit; Yogendra Singh; Seemi Farhat Basir; Taruna Madan (Mycopathologia, 2012)

CaCl2 improves post-drought recovery potential in Camellia sinensis (L) O. Kuntze - Hrishikesh Upadhyaya; Sanjib Kumar Panda; Biman Kumar Dutta (Plant Cell Reports, 2011)

Variation of physiological and antioxidative responses in tea cultivars subjected to elevated water stress followed by rehydration recovery - Hrishikesh Upadhyaya; Sanjib Kumar Panda; Biman Kumar Dutta (Acta Physiologiae Plantarum, 2008)